2021
DOI: 10.3390/jof7121006
|View full text |Cite
|
Sign up to set email alerts
|

Marine Macroalgae, a Source of Natural Inhibitors of Fungal Phytopathogens

Abstract: Fungal phytopathogens are a growing problem all over the world; their propagation causes significant crop losses, affecting the quality of fruits and vegetables, diminishing the availability of food, leading to the loss of billions of euros every year. To control fungal diseases, the use of synthetic chemical fungicides is widely applied; these substances are, however, environmentally damaging. Marine algae, one of the richest marine sources of compounds possessing a wide range of bioactivities, present an eco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 121 publications
(171 reference statements)
0
13
0
2
Order By: Relevance
“…There are many accounts of bioactive composites resulting from macroalgae as a promising supply of biochemical and medical characteristics comprising antibacterial [39], antifungal [40], antiviral [41], antioxidant [42], and anti-inflammation [43] activities. Furthermore, the percentage of fungal mycelia decline in this study emphasizes the presence of bioactive compounds in the extracts of the macroalgae tested, which can be resolvable in solvents, and may be related to the high concentration in organic extracts against microorganisms [44]. Many researchers described the antifungal activity of some macroalgae against FOL in vivo and in vitro [45,46].…”
Section: Discussionmentioning
confidence: 66%
“…There are many accounts of bioactive composites resulting from macroalgae as a promising supply of biochemical and medical characteristics comprising antibacterial [39], antifungal [40], antiviral [41], antioxidant [42], and anti-inflammation [43] activities. Furthermore, the percentage of fungal mycelia decline in this study emphasizes the presence of bioactive compounds in the extracts of the macroalgae tested, which can be resolvable in solvents, and may be related to the high concentration in organic extracts against microorganisms [44]. Many researchers described the antifungal activity of some macroalgae against FOL in vivo and in vitro [45,46].…”
Section: Discussionmentioning
confidence: 66%
“…Tảo nâu Dictyopteris polypodioides (D. polypodioides) là một trong những cây dược liệu thuộc họ Dictyopteris, phân bố rộng rãi ở các vùng biển nhiệt đới, cận nhiệt đới Châu Á. Kết quả nghiên cứu của Kolsi et al (2017) đã cho thấy cao chiết methanol (MeOH) Tảo nâu D. polypodioides có hiệu quả ức chế enzyme α-amylase rất cao lên đến 86,34% ở nồng độ 200 µg/mL. Gần đây, zonarol, sesquiterpene hydroquinone, được phân lập từ chiết xuất methanol của họ Dictyopteris, đã được công bố có hiệu quả sinh học đáng kể như ức chế phospholipase (Mayer et al, 1993), chống oxy hóa (Lee et al, 2013), chống viêm (Yamada et al, 2014), kháng khuẩn (Akremi et al, 2017) và kháng nấm (Vicente et al, 2021). Vì vậy, khả năng sàng lọc được các hoạt chất tự nhiên có hoạt tính sinh học ở Tảo nâu D. polypodioides là rất lớn.…”
Section: Giới Thiệuunclassified
“…Ghi chú: giá trị phần trăm gây ức chế ở từng phân đoạn với các mẫu tự khác nhau đại diện cho sự khác biệt ở mức ý nghĩa 5% Zonarol là một hợp chất có cấu trúc vòng parahydroquinone, được phân lập và chiết xuất từ dung môi methanol của họ Tảo nâu Dictyopteris và xác định rõ cấu trúc hóa học lần đầu tiên năm 1986 (Fenical et al, 1973;Mori & Komatsu, 1986). Một số tác dụng dược lý của hợp chất zonarol đã được công bố như hiệu quả kháng nấm, kháng khuẩn, kháng oxy hóa (Lee et al, 2013;Yamada et al, 2014;Akremi et al, 2017;Vicente et al, 2021). Kết quả nghiên cứu của Yamada et al (2014) cho thấy zonarol biểu hiện hoạt tính kháng viêm mạnh trên mô hình chuột được gây viêm ruột bằng dextran sulfate sodium (DSS) với hiệu quả tương đương với chất chuẩn 5-aminosalicylic acid (5-ASA).…”
Section: Hình 3 Phần Trăm Gây ứC Chế Enzyme α-Amylase Và α-Glucosidas...unclassified
“…In the last decades, it has been increasingly reported that marine organisms synthesize a vast number of bioactive secondary metabolites with promising biotechnological applications [ 15 ]. It is estimated that seaweeds synthesize around 40,000 different compounds with antifungal activity, including polysaccharides, polyphenols, carotenoids, proteins, peptides, sterols, terpenes, and fatty acids [ 15 , 16 , 17 ]. Throughout the last century, both in vitro and in vivo assays were carried out (making use of mycelium, spores, and infected plants), showing variations in the antimicrobial activities depending on the seaweed (influenced by environmental and biological factors), the extraction method, and the solvents used [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that seaweeds synthesize around 40,000 different compounds with antifungal activity, including polysaccharides, polyphenols, carotenoids, proteins, peptides, sterols, terpenes, and fatty acids [ 15 , 16 , 17 ]. Throughout the last century, both in vitro and in vivo assays were carried out (making use of mycelium, spores, and infected plants), showing variations in the antimicrobial activities depending on the seaweed (influenced by environmental and biological factors), the extraction method, and the solvents used [ 17 ]. It has been proven that different seaweed macerates and extracts are able to fight phytopathogenic fungi not only inhibiting or reducing the growth of their vegetative hyphae or attacking them by lytic enzymes but also inhibiting the germination of their conidia (mycostatic activity) [ 18 ].…”
Section: Introductionmentioning
confidence: 99%